A narrative exploration of an adapted physical activity space and its impact on persons with physical impairments. Issue 1 (2nd January 2020) - Richardson, Emma V.; Motl, Robert W.
Abstract: The Lakeshore Foundation is a community-based rehabilitation facility that claims to be fully adapted to support persons with physical impairments in exercise endeavors. The dominant narratives of ableism that can exclude persons with physical impairments from non-adapted exercise spaces supports research that explores narratives told in adapted exercise spaces. To explore the Lakeshore narrative and its effects, we conducted 35 semi-structured interviews with Lakeshore members and subjected these data to a dialogical narrative analysis. We crafted a story that reflected the participants' journey from poor health to a sense of well-being. On this journey, participants discussed feeling included, that their body was accepted, like works in progress, part of a family, progression from story listeners to story-tellers and well-being. This journey to well-being highlights the important role that adapted exercise spaces can have on enhancing the well-being of individuals with physical impairments.